Frequency response based curve fitting approximation of fractional-order PID controllers - Bingi, Kishore; Ibrahim, Rosdiazli; Karsiti, Mohd Noh; Hassam,Sabo Miya; Harindran, Vivekananda Rajah (Zielona Góra: Uniwersytet Zielonogórski)
Fractional-order PID (FOPID) controllers have been used extensively in many control applications to achieve robust control performance. To implement these controllers, curve fitting approximation techniques are widely employed to obtain integer-order approximation of FOPID. The most popular and widely used approximation techniques include the Oustaloup, Matsuda and Cheraff approaches. However, these methods are unable to achieve the best approximation due to the limitation in the desired frequency range.
Keywords: curve fitting; fractional-order PID controller; Frequency Response Function; integer-order approximation; Oustaloup approximation; Matsuda approximation